Probing the hydrophilicity of coir fibres: analysis of the mechanical properties of single coir fibres. (2017) - Thomas, Sabu; Woh, Yu-Ker; Wang, Rachel; Goh, Kheng Lim
Abstract: This study investigates the mechanical properties of dry versus fully hydrated single micrometre-thick coir fibres. The motivation is to gain insights into the hydrophilicity of the fibres. Specimens of coir fibres were subjected to tensile test until rupture using a horizontal environmental micromechanical tester, mounted on an inverted microscopy for simultaneous microscopy and mechanical testing. The hydrated specimens were submerged in water held in a Petri-dish, mounted onto the tester, for continuous hydration during the test by. Statistical analysis shows strong evidence of differences in the following parameters. The mean fibre diameter of the wet specimens is larger than the dry specimens. The mean tensile stiffness and fracture strength of the dry specimens is larger than the wet specimens. However, the fibre extensibility yields no evidence of differences. A probability strength analysis reveals that while the dry fibre has a higher characteristic strength than the wet fibre, the wet fibre exhibited a smaller spread of variability in strength than the dry fibre.